How the Crisis Changed the Pace of Poverty Reduction and Shared Prosperity : Armenia Poverty Assessment - World Bank Group (World Bank, Washington, DC, 2016)
This report examines Armenia’s experience in reducing poverty and raising the welfare of the least well-off in the country in the years since 2009. What households spend on consumption is an indicator of their welfare. As the economy recovered from crisis, the least well-off enjoyed some growth in consumption spending, but not as much as in the years up to 2009. Moreover, growth has become less pro-poor in relative terms because the less well-off enjoyed lower growth in consumption than the better-off. As a result, although consumption did translate into a reduction in poverty, inequality is now higher than before 2009. In 2013, 32 percent of Armenia’s population lived below the national poverty line, a poverty rate higher than in pre-crisis years but down from the high of 35.8 percent in 2010. In fact, between 2012 and 2013, poverty reduction seems to have stalled. This report looks at the micro and macro aspects of Armenia’s poverty reduction experience to: (a) describe the key features of post-crisis poverty, inequality, and consumption growth; (b) examine the drivers of poverty reduction in this period; and (c) explore reasons why future growth might not be as pro-poor as in the past.